Qanan: Food Processing in the Culture of the Tehit People in West Papua - Flassy, Marlina; Saa, Septinus; Frank, Simon Abdi Kari (ETNOSIA : Jurnal Etnografi Indonesia, 2022)
This article discusses about qanan which is a way to cook food that is typical for the Tehit tribe. Cooking patterns using qanan bark are not done every day, but only carried out on special rituals, for example, traditional, religious, and government events. The cooking begins with the preparation of meat, mixed with green spices and vegetables. The mixed ingredients that have been seasoned is arranged in the bark that has been dialed into the inside then tied with a rattan strap and roasted on a flame. The baked cooking material was rotated until the wooden skin was black. The surface appearance of black bark is an indicator of cooked meat and vegetables. Furthermore, when the bark is opened, meat and vegetables are removed and ready to be served. We use qualitative research methods in this study, with literature studies, observation, and interviews as data collection methods. The results show the wealth of knowledge and local wisdom of the Tehit ethnic group in processing food traditionally by the method of wrapping food using bark which is known as qanan. The taste of the food processed with the technique has the aroma of bark combined with the addition of spices that seep into the meat and vegetables. In addition, hot steam from combustion causes food to cook quickly and not scorched, and the process of maturation of food ingredients occurs evenly and delicious. The local wisdom of the Tehit people in the land of Papua is the wealth of Indonesia that must be maintained and preserved because the pattern of cooking Qanan is quite healthy since it does not use cooking oil. Patterns of local food processing in Tehit culture can be used as one of the strategies for overcoming cooking oil scarcity.